The Influence of Work Environment and Work Motivation on Employee Performance at Pt. Pamor Ganda Bengkulu Utara - Siboro, Nadia Sauli Yanti Br.; Made, Ida Ayu; Nurzam, Nurzam (Jurnal Bisnis, Manajemen dan Akuntansi, 2026)
Human resources play an important role in achieving company goals. The success of a company is not only determined by technology and capital, but also by the abilities and motivation of its employees. A comfortable working environment and high work motivation can improve employee performance. However, at PT Pamor Ganda Bengkulu Utara, there is still a suboptimal working environment and varying levels of work motivation, which can affect employee performance. This study aims to determine the effect of the work environment and work motivation on employee performance at PT Pamor Ganda Bengkulu Utara. This study uses a quantitative approach with a survey method of 111 respondents using a Likert scale questionnaire. Data analysis uses multiple linear regression with the equation Y = 9.704 + 0.209X₁ + 0.528X₂. The results show that the work environment has a positive and significant effect on employee performance (tcount 2.732 > ttable 1.982; sig. 0.007 < 0.05) and work motivation also has a positive and significant effect on employee performance (tcount 7.186 > ttable 1.982; sig. 0.000 < 0.05). The simultaneous test shows Fcount 59.385 > Ftable 2.76 with significance 0.000 < 0.05, so it can be concluded that the work environment and work motivation together have a significant effect on employee performance at PT Pamor Ganda Bengkulu Utara.